# Solve for w 5+2(5w-1)=-3(2w-5)+7

5+2(5w-1)=-3(2w-5)+7
Simplify 5+2(5w-1).
Simplify each term.
Apply the distributive property.
5+2(5w)+2⋅-1=-3(2w-5)+7
Multiply 5 by 2.
5+10w+2⋅-1=-3(2w-5)+7
Multiply 2 by -1.
5+10w-2=-3(2w-5)+7
5+10w-2=-3(2w-5)+7
Subtract 2 from 5.
10w+3=-3(2w-5)+7
10w+3=-3(2w-5)+7
Simplify -3(2w-5)+7.
Simplify each term.
Apply the distributive property.
10w+3=-3(2w)-3⋅-5+7
Multiply 2 by -3.
10w+3=-6w-3⋅-5+7
Multiply -3 by -5.
10w+3=-6w+15+7
10w+3=-6w+15+7
10w+3=-6w+22
10w+3=-6w+22
Move all terms containing w to the left side of the equation.
Add 6w to both sides of the equation.
10w+3+6w=22
16w+3=22
16w+3=22
Move all terms not containing w to the right side of the equation.
Subtract 3 from both sides of the equation.
16w=22-3
Subtract 3 from 22.
16w=19
16w=19
Divide each term by 16 and simplify.
Divide each term in 16w=19 by 16.
16w16=1916
Cancel the common factor of 16.
Cancel the common factor.
16w16=1916
Divide w by 1.
w=1916
w=1916
w=1916
The result can be shown in multiple forms.
Exact Form:
w=1916
Decimal Form:
w=1.1875
Mixed Number Form:
w=1316
Solve for w 5+2(5w-1)=-3(2w-5)+7

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top